Autonomous vehicle navigation using high-definition maps through CARLA-ROS simulator bridge. Issue 1 (1st August 2022) - Fatima, H. Sundus; Abbas, Ammar N.; Bawany, Faraz; Zia, Huma; Yusuf, Syed Adnan; Khurram, Muhammad
Abstract: Autonomous vehicles (AV) have garnered significant interest in recent years due to its potential for controlling thousands of accidents that happen yearly due to human error. However, AV bring with it very complex and sophisticated requirements and challenges related to extensive testing of the algorithms and hardware in the physical world. The evolution of automotive simulation tools provides an opportunity to fully test and validate AV architectures without the risk of creating hazardous situations in real world. This research demonstrates the application of HD (High Definition) maps in autonomous vehicle navigation using ROS interface integrated with the CARLA (CAR Learning to Act) simulator. The sensor data includes Light Detection and Ranging (LiDAR), RGB-Depth (RGB-D), and vehicle odometry. HD maps play an important role in robustness of the autonomous systems where due to sensor obstruction or weather conditions the vehicle is unable to perceive the information ahead. It also aids the vehicle to sense its environment even outside from the sensor's field of view. The research is divided into the three fundamental concepts of Simultaneous Localization and Mapping (SLAM) approach that is, (i) mapping, (ii) localization, and (iii) navigation. Two ROS tools are used for mapping, (a) OctoMap mapping, and (ii) Real-Time Appearance-Based Mapping (RTAB-Map). We demonstrate the effectiveness of localization using RTAB-Map and compare actual path, position and orientation to their estimated equivalents. Our results show acceptable error in XY axes and exemplifies the error accumulated in Z axis.